"How do you measure the loss of a lake?": Assessing community relevance of health impact assessment frameworks to the Tl'azt'en nation of northern-interior British Columbia. - Mackie, Jennifer H. (Author); Leeuw, Sarah de (Thesis advisor); Harder , Henry (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
The purpose of this research was to critically engage a contemporary means by which impacts to Indigenous health are gauged during federal and/or provincial environmental assessments (EAs). Specifically, I was interested in the utility of health impact assessments (HIAs) conducted during environmental assessments, which concern the effects of mining on First Nations communities. For this research, I dialogued with participants from the Tl'azt'en nation in order to learn their opinions and concerns about the impact of industrial development on health from an Indigenous world-view perspective. An Indigenous methodological research design was followed and participants were recruited to share their perspectives on health impact assessments in a focus group setting. From stories and narratives gathered during these focus group sessions, themes emerged that I argue must form a foundation for future health impact assessments. If rooted within the context of the Indigenous nation, the health impact assessment might accurately and justly represent Indigenous health realities in terms of the negative changes(s) that industrial development may create on unceded Indigenous lands. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1803097